Application of the Principle of Restorative Justice to the Termination of Investigation Warrant (SP3) - Agus Susanto (Budapest International Research and Critics University, 2022)
The purpose of this study is to find out how to apply the principle of restorative justice to the warrant for termination of investigation (SP3). The research method used is a normative legal research method. The legal sources used are from the Legislation and secondary legal materials along with other legal sources.